Smart responsive microneedles for controlled drug delivery - Qi, Zhenzhen (2023)
As an emerging technology, microneedles offer advantages such as painless administration, good biocompatibility, and ease of self-administration, so as to effectively treat various diseases, such as diabetes, wound repair, tumor treatment and so on. How to regulate the release behavior of loaded drugs in polymer microneedles is the core element of transdermal drug delivery. As an emerging on-demand drug-delivery technology, intelligent responsive microneedles can achieve local accurate release of drugs according to external stimuli or internal physiological environment changes. This review focuses on the research efforts in smart responsive polymer microneedles at home and abroad in recent years. It summarizes the response mechanisms based on various stimuli and their respective application scenarios. Utilizing innovative, responsive microneedle systems offers a convenient and precise targeted drug delivery method, holding significant research implications in transdermal drug administration. Safety and efficacy will remain the key areas of continuous efforts for research scholars in the future.